Mindful Parenting and Subjective Well-Being in Parents of Children with Neurodevelopmental Disorders - Maharani, Anisa Putri Primi Intan; Rinaldi, Martaria Rizky (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2024)
Parenting children with neurodevelopmental disorders presents unique challenges. These challenges can impact the well-being of parents, leading to higher levels of stress, anxiety, and depression, which ultimately can lower subjective well-being. This study aims to investigate the relationship between mindful parenting and subjective well-being using a correlational quantitative approach. Data were collected through questionnaires measuring mindful parenting and subjective well-being. The participants in this study were 106 parents of children with neurodevelopmental disorders. Data analysis was conducted using the product-moment correlation technique. The results indicated a positive correlation (r = 0.413, p 0.05) between mindful parenting and subjective well-being, suggesting that higher levels of mindful parenting are associated with higher subjective well-being in parents. These findings highlight the potential of mindful parenting interventions to support the well-being of parents in families with children with special needs. Future research should use larger and more representative samples to enhance the generalizability of the findings. The implications of this research include the development of mindful parenting programs and policies to support families facing the challenges of raising children with neurodevelopmental disorders.